Potential of Jatropha Curcas Seed Extract Linimentum as A Therapeutic for Scabies in Goats - Said, Nur Saidah; Marsudi, Marsudi; Fahrodi, Deka Uli (Jurnal Agripet, 2025)
This study aimed to evaluate the potential of Jatropha curcas seed extract liniment (JSE) as a therapeutic agent for scabies in goats. The experiment involved 20 adult goats (1215 months old) divided into five treatment groups: P0 (negative control), P1 (positive control), P2 (10% JSE), P3 (20% JSE), and P4 (40% JSE). Each treatment group consisted of four replicates, with one goat per replicate. The JSE preparation was applied topically to the affected skin twice daily (morning and evening) for 14 days. Data were collected on days 0, 3, 7, 10, and 14, assessing clinical parameters such as alopecia, skin thickening, scab formation, and scabies recovery time. The results indicated that the 40% JSE treatment (P4) exhibited superior efficacy compared to lower concentrations, yielding outcomes comparable to the positive control (ppt sulfur liniment), a widely used scabies treatment.